Judicial constitutional control In Russia and foreign countries: models, significance and specificity - F. S. Bekirova; R. R. Gabrilyan (Гуманитарные и юридические исследования, 2024)
Introduction. Constitutional review is the cornerstone in maintaining the constitutional order, ensuring compliance with the rule of law and protecting individual rights in the state. Differences in models of constitutional review globally highlight its complexity and uniqueness. This factor necessitates a comparative study to reveal the specific mechanisms used in different legal systems. The article examines the models, significance and features of constitutional control In Russia and a number of foreign countries, determines the nuances of their functioning, as well as issues of interaction between the elements of constitutional control models. Materials and Methods. During the comparative legal analysis, the practice of functioning of constitutional control In Russia, the USA, Germany, Austria, France, Canada and Australia was studied. The primary sources were national constitutions, legislation, as well as landmark judicial decisions in several states. Secondary sources of research are scientific literature: monographs, periodical articles and expert analytical documents. A mixed approach facilitates a thorough examination of the structure and functions of constitutional review bodies in a broader political and legal context. Analysis. The study examines various models of constitutional review, in particular, the European (centralized Kelsen model), adopted In Russia, Germany and Austria, is compared with the American model (decentralized model of constitutional control in the USA), the hybrid (mixed) systems of Canada and Australia, which have regional features and combine elements of the American and European models, as well as the French model with its quasijudicial bodies of constitutional control. The comparative analysis is carried out according to several criteria, while covering the problems faced by systems of constitutional control. Results. A comparative study reveals various paradigms of constitutional control. Their examination determines to what extent the independence of the institutions of constitutional review critically affects the effectiveness of the work of constitutional review bodies, and which models demonstrate vulnerability from political influence. The need to ensure greater autonomy for constitutional review bodies and facilitate access to constitutional mechanisms is emphasized. The multifaceted nature of constitutional review is highlighted and an opinion is expressed on the possibility of further improving the institutions of constitutional review.